Experimental and numerical study on the mechanical properties of embedded double-row-pins connectors. (January 2022) - Cheng, Chen; Wan, Shui; Song, Aiming
Abstract: In the structure of prestressed concrete box-girder bridge with corrugated steel web, the shear connectors are arranged to ensure the concrete slab and corrugated steel web work together. For the headed stud connector and PBL connector, the flange plates are arranged on the upper or lower edges of the steel webs, so the concrete slab is not easy to be vibrated during the bridge construction, resulting in insufficient compaction of concrete. For the embedded connector, to solve this problem, no flange plates are installed on the edges of corrugated steel webs. However, the embedded connector's ultimate shear load is smaller than that of headed stud connector and PBL connector. The connector's essence is the reinforced concrete pin. Therefore, compared with other structural measures, increasing the reinforced concrete's number is more effective to improve the ultimate shear load of connectors. The ultimate shear load of embedded double-row-pins connector is improved due to arranging two rows of reinforced concrete pins. In this paper, 45 push-out specimens of embedded connector were designed and loaded to failure. The failure mode, shear capacity and shear stiffness of the embedded double-row-pins connector were studied. Furthermore, 44 nonlinear finite element models were performed to study the effects of structural geometric parameters and concrete strength. The parametric results were generated to evaluate these parameters's influence on the ultimate shear load of embedded double-row-pins connector. At last, a equation was genrated to predict the ultimate shear load of the embedded double-row-pins connector.